Foreign direct investment effect on economic growth in ASEAN countries (2002 - 2019) - Htoo, Htet Htet (KDI School, 2022)
The determination of our empirical investigation is to study the foreign direct investment (FDI) effect on ASEAN's economic growth utilizing human capital. Moreover, our empirical investigation aims to investigate how FDI interacts with domestic investment, human capital, and trade in developing countries to promote economic growth. The World Bank Indicators is the source of data obtained for the period of year 2002 to 2019 and OLS approach was used to analyze. One of the most important components in the development of a successful economy is human capital. Although FDI has favorable impact on ASEAN economic growth, human capital, domestic investment, and trade don’t have positive effect in ASEAN countries. This research’s conclusive finding is FDI effects on economic growth are independent of the human capital level of the host country. It can be concluded that the higher the quality of a country's human capital, the greater its economic growth and FDI inflows will be.
Thesis(Master) -- KDI School: Master of Development Policy, 2022
Keywords: Investments, Foreign--Southeast Asia; Economic development--Southeast Asia